A Critical Reflection on Digital Literacy Skills and its Impact on Information Seeking Behavior of Small-Scale Women Farmers in Muvuti Kiima Kimwe, Kenya - Muia, Boniface; Kimani, Grace (International Journal of Current Aspects, 2025)
The study aimed to investigate the influence of digital literacy on information seeking behavior of small-scale women farmers in Muvuti Kiima Kimwe, Kenya. Utilizing The Big 6 Skills Model developed by Eisenberg and Berkowitz in 1987 as a framework, the study adopted a descriptive research design, allowing for the concurrent collection of both qualitative and quantitative information. The study’s target population was approximately 17,059 small-scale women farmers from Muvuti Kiima Kimwe ward. Purposive sampling method was employed to select 143 small-scale women farmers. Data was collected using questionnaires which had both open and closed ended questions. Qualitative data from open-ended questions were examined through content analysis, while quantitative data were analyzed using descriptive statistics with the assistance of SPSS version 26. Small-scale women farmers indicated that they needed information to improve their agricultural activities. The study findings revealed that majority of the small-scale women farmers have never attended digital literacy training and have inadequate knowledge on how to seek for digital information and therefore they enlist the help of family members or friends. The government, through the Ministry of Information, Communications and Digital Economy, need to formulate clear policy aimed to initiate digital literacy training programs in rural areas targeting small-scale women farmers as a means for improving digital literacy in rural areas.
Keywords: Digital literacy, information seeking behavior, information need, small-scale women farmer.